Heterozygous PLA2G6 Mutation Leads to Iron Accumulation Within Basal Ganglia and Parkinson's Disease - Rosangela Ferese; Simona Scala; Francesca Biagioni; Emiliano Giardina; Emiliano Giardina; Stefania Zampatti; Stefania Zampatti; Nicola Modugno; Claudio Colonnese; Claudio Colonnese; Marianna Storto; Francesco Fornai; et al. (Frontiers in Neurology, 2018)
Mutations of PLA2G6 gene are responsible for PARK14, an autosomal recessive L-DOPA responsive dystonia/parkinsonism with early/adult onset. This phenotype possesses an high clinical variability, which consists in the occurrence of cerebral and cerebellar atrophy, iron accumulation in the basal ganglia, and cognitive decline. This report describes a PD patient carrying an heterozygous PLA2G6 mutation, which was identified also in his PD affected sister. This patient is characterized by a L-DOPA responsive typical parkinsonian syndrome without the occurrence of dystonia, a slight cognitive decline, presence of iron accumulation both in neo and paleostriatum while cerebellar atrophy was absent. Clinical and imaging features are compatible with the PARK14 phenotype. Although PARK14 has been previously reported to be inherited as a recessive disorder, clinical and genetic analysis of this proband and his family rise the hypothesis that even heterozygous PLA2G6 mutations may cause PARK14. It remains to be analyzed whether these heterozygous variants may act as dominant mutations, or they merely increase the risk to develop PD by acting within a context of synergistic genetic and/or environmental backgrounds.